Orthodox macroeconomic textbooks: A critical evaluation using institutional practice as a benchmark. (June 2021) - Juniper, James; Nadolny, Andrew; Pantelopoulos, George; Watts, Martin
Abstract: Many heterodox economists advocate the adoption of pluralist teaching strategies in universities, citing the benefits of developing the capacity of students to engage in critical thinking. However, with the dominance of orthodox macroeconomic thinking and increasing career pressures associated with the need to publish in leading mainstream journals, many teachers have become reliant on a limited number of orthodox macroeconomics textbooks. This paper explores how a small sample of leading introductory macroeconomics textbooks have responded to the challenges to orthodox macroeconomic thinking in the last decade or so since the Global Financial Crisis. We focus on the definitions of concepts and the consistency of the theoretical and policy frameworks, in the light of the insights about what we define as Institutional Practice. This concept refers to the way that the Central Bank, Treasury and commercial banks actually operate in modern monetary economies, as described by employees of international agencies such as the IMF and the European and national Central Banks. We also draw implications of our work for the teaching of undergraduate macroeconomics.